2018
DOI: 10.1039/c8ra01674g
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted Article: Ligustrazine attenuates renal damage by inhibiting endoplasmic reticulum stress in diabetic nephropathy by inactivating MAPK pathways

Abstract: Diabetic nephropathy (DN) is a major cause of chronic kidney disease around the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
(39 reference statements)
1
7
0
Order By: Relevance
“…Our findings are just consistent with previous studies, and illustrate that the inflammatory response is relieved by the up-regulation of miR-451 in H-GMCs. In addition, it has been proved that some agents exhibit great potential in the treatment of DN via inhibiting pro-inflammatory cytokines, such as resveratrol [28], ligustrazine [29], notoginsenoside R1 [30], and ellagic acid [15]. We suspect that the up-regulation of miR-451 may protect against DN through relieving inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are just consistent with previous studies, and illustrate that the inflammatory response is relieved by the up-regulation of miR-451 in H-GMCs. In addition, it has been proved that some agents exhibit great potential in the treatment of DN via inhibiting pro-inflammatory cytokines, such as resveratrol [28], ligustrazine [29], notoginsenoside R1 [30], and ellagic acid [15]. We suspect that the up-regulation of miR-451 may protect against DN through relieving inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…The PI3k/Akt/mTOR signaling pathway is currently known as the only inhibitory pathway for autophagy, and its activation can inhibit autophagy. Zhong et al [ 35 ] found that ligustrazine can inhibit the expression of p-PI3K, p-Akt, and p-mTOR in the kidney tissues of diabetic rats, thereby, increasing the expression level of the autophagy marker protein LC3B and the ratio of LC3B-II/LC3B-I. The results of this experiment indicate that the PI3k/Akt/mTOR signaling pathway is activated, and autophagy is inhibited in diabetic nephropathy; however, the signaling pathway is inhibited, and autophagy is reactivated after GLP treatment, indicating that GLP plays a renal protective role.…”
Section: Discussionmentioning
confidence: 99%
“…In the year 2018, several compounds like berberine, gallic acid, ligustrazine, nifuroxazide, pentoxifylline, rosuvastatin, and so forth to treat kidney damage in type 1 diabetes and compounds like dihydroquercetin, cinacalcet, cyanidin‐3‐O‐glucoside, zingerone, glucagon‐like peptide‐1 (GLP‐1) co‐agonist, dapagliflozin, pioglitazone, and fibroblast growth factor 1 to treat kidney damage in type 2 diabetes have been studied so far. Compound like carnosic acid was found to ameliorate kidney damage in both type 1 and type 2 diabetes (Ding et al, ; Elhawary, Ibrahim, & Attallah, ; Elsherbiny, Zaitone, Mohammad, & El‐Sherbiny, ; Garud & Kulkarni, ; Han et al, ; Liang et al, ; Lim et al, ; Patel et al, ; Qin et al, ; Rehman et al, ; Xie et al, ; Yang & Wu, ; Zhu, Han, Yuan, Xue, & Pang, ).…”
Section: Introductionmentioning
confidence: 99%